Notes on some rare Hesperiidae from Miao Range, Namdapha National Park, Arunachal Pradesh, India (Insecta: Lepidoptera) - Renu Gogoi; Roshan Upadhaya; Ruksha Limbu; Rezina Ahmed (SHILAP, 2024)
Namdapha National Park is home to a wide variety of species located in Changlang district of Arunachal Pradesh state in North-East India. The park is flanked by the Patkai hills to the South and by the Himalaya in the North and lies close to the Indo-Myanmar-China trijunction. Here we reported the occurrence of 14 rare Hesperiidae from the park namely Plastingia naga (Nicéville, 1884), Pyroneura margherita (Doherty, 1889), Salanoemia noemi (Nicéville, 1885), Lotongus sarala (Nicéville, 1889), Hidari bhawani (Nicéville, 1888), Matapa sasivarna (Moore, 1866), Thoressa hyrie (Nicéville, 1891), Burara amara (Moore, 1866), Burara gomata (Moore, 1866), Burara jiana (Moore, 1866), Bibasis sena (Moore, 1866), Odina decorates (Hewitson, 1867), Mooreana trichoneura (Felder, 1860) and Darpa hanria (Moore, 1881).